2021
DOI: 10.1111/jcal.12584
|View full text |Cite
|
Sign up to set email alerts
|

Smart mechanisms and their influence on geometry learning of elementary school students in authentic contexts

Abstract: With facilitation of advanced technologies, design and application of smart become promising research issues in education. Although it is potential for students to learn geometric in authentic contexts, there were still lack of studies addressing smart learning issue in authentic context for geometry. This study aim to propose an app, called SmartUG, to support students smartly to consolidate geometry understanding and learning through enriching experience of exploring and applying related geometry surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…Students may be able to practice and perfect their English pronunciation without encountering any obstacles if they use speech recognition software and receive some assistance from artificial intelligence (AI) (Hwang et al, 2022). In a different piece of research, Hwang et al (2021) hypothesized that students could learn geometric concepts that are contextually relevant to their lives if they were taught in real-world situations using AI for shape identification. In particular, the researchers thought that students could learn these concepts if they were taught how to identify shapes using AI.…”
Section: Changes In Views On What Schooling Ought To Domentioning
confidence: 99%
See 1 more Smart Citation
“…Students may be able to practice and perfect their English pronunciation without encountering any obstacles if they use speech recognition software and receive some assistance from artificial intelligence (AI) (Hwang et al, 2022). In a different piece of research, Hwang et al (2021) hypothesized that students could learn geometric concepts that are contextually relevant to their lives if they were taught in real-world situations using AI for shape identification. In particular, the researchers thought that students could learn these concepts if they were taught how to identify shapes using AI.…”
Section: Changes In Views On What Schooling Ought To Domentioning
confidence: 99%
“…In particular, the researchers thought that students could learn these concepts if they were taught how to identify shapes using AI. According to the studies conducted (Hwang et al, 2021(Hwang et al, , 2022 conducted, using technology in the classroom helps increase students' academic performance and also helps keep students motivated. Due to participating in this training, the NLP has significantly enhanced its capacity to read human language.…”
Section: Changes In Views On What Schooling Ought To Domentioning
confidence: 99%
“…For example, recognition technologies, such as speech recognition and the support of AI could accommodate learners to practice pronouncing English texts independently [18]. A different study suggested that learners could learn geometry meaningfully in their surroundings as the learning contexts are defined as authentic contexts with the recognition of geometric objects through AI [19]. These studies also demonstrated that the implementation of technology in education can sustain the learners' motivation and enhance learning achievement [18,19].…”
Section: The Shifting Perspective On Educationmentioning
confidence: 99%
“…,Amir et al (2020),Hwang et al (2021b) danBhagat et al (2021). Keseluruhannya menunjukkan kesan yang positif dan membantu murid lebih memahami dalam pembelajaran geometri.…”
unclassified